Pelatihan Pembuatan Laporan Keuangan Sederhana bagi Pelaku UMKM Kabupaten Paser Kalimantan Timur - Norsita, Mega; Yuliana; Yusuf, Abdurrahman Maulana; Sudirman, Sitti Rahma; Harseno, Diah Fitri (Jurnal Abdi Masyarakat Nusantara, 2025)
Abstract Micro, Small, and Medium-Sized Enterprises (MSMEs) are companies that support Indonesia's economic growth. According to the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia (2017), MSMEs can employ 97% of the country's workforce and account for about 60% of its GDP. However, the creation of financial reporting for the MSME sector is a basic issue that MSME operators must deal with. The implementation of SAK EMKM-based financial reporting requirements has presented MSMEs with an adaptation challenge. This community service project aims to raise awareness of modified SAK EMKM-based MSME financial reporting. Keywords: MSMEs, SAK EMKM, Financial Statements of MSMEs